The Incidence and Significance of Bovine Herpesvirus (infectious bovine rhinotracheitis) Antibodies in the Sera of Aborting Cattle - Mitchell, D. (1967)
The results of bovine herpesvirus (IBR-IPV) neutralization tests conducted on the sera of 463 animals with a prior history of undiagnosed abortion and 331 control animals with no history of abortion are reported. One hundred and thirty-one (28.3 per cent) of the aborting and 105 (31.7 per cent) of the control animals, were found to harbour antibody to this virus. No significant seasonal or gestational incidence could be determined but some variation in the annual incidence was apparent. On the basis of these results it appears unlikely that this virus is responsible for a significant proportion of the undiagnosed cases of bovine abortion in Quebec and Ontario, where the animals tested were located. The problems involved in substantiating a diagnosis of abortion due to bovine herpesvirus are briefly discussed.